Entropy-Guided Assessment of Image Retrieval Systems: Advancing Grouped Precision as an Evaluation Measure for Relevant Retrievability (Informatica, 2023)
The performance evaluation of Content Based Image Retrieval systems (CBIR), can be considered as a challenging and overriding problem even for human and expert users regarding the important numbers of CBIR systems proposed in the literature and applied to different image databases. The automatic measures widely used to assess CBIR systems are inspired from the general Text Retrieval (TR) domain such as precision and recall metrics. This paper proposes a new quantitative measure adapted to the CBIR particularity of relevant images grouping, which is based on the entropy of the returned relevant images. The proposed performance measure is easy to understand and to implement. A good discriminative power of the proposed measure is shown through a comparative study with the existing and well-known CBIR evaluation measures.